O?itun W? O?in, O?in W? O?itun, Gender Roles Reversal and the Bane of Modernization: Lessons from the Past - Samuel Kayode Olaleye; Oluwatoyin Adebola Gbadamosi; Julius Sunday Adekoya (Journal of Research in Social Science and Humanities, 2026)
Gender Roles definitions have played prominent parts in families and the society at large, influencing the training giving to children, as boys or girls, prompting their actions in the future. As modernity is embraced, the lines demarcating the gender roles became blurry and some of these roles were reversed, interchanged or were totally non-existent. With the influence of Western culture, some expectations previously gender tied within the family setting became outdated. Ancient African societies had symbiotic family relationships expressed in Yoruba as O??tu?n we? o?si?, o?si? we? o??tu?n,- the right washes the left and the left washes the right in the case of hand washing, which symbolically means that both hands are important to each other. This paper, therefore, examined the trend of gender roles reversals in today’s world by juxtaposing them with what obtained in the past with the view of drawing lessons for successful family living. Primary data was gathered from in-depth interviews conducted with 20 Yoruba elders versed in Yoruba culture and 20 married Yoruba Youths. A structured questionnaire was administered and responses from 73 respondents were gathered. The qualitative data were content analysed while the quantitative data were analysed descriptively using simple percentages.